Very simple Markov-perfect industry dynamics - Jaap H. Abbring; Jeffrey R. Campbell; Jan Tilly; Nan Yang (Federal Reserve Bank of Chicago, 2013)
This paper develops an econometric model of industry dynamics for concentrated markets that can be estimated very quickly from market-level panel data on the number of producers and consumers using a nested fixed-point algorithm. We show that the model has an essentially unique symmetric Markov-perfect equilibrium that can be calculated from the fixed points of a finite sequence of low-dimensional contraction mappings. Our nested fixed point procedure extends Rust's (1987) to account for the observable implications of mixed strategies on survival. We illustrate the model's empirical application with ten years of County Business Patterns data from the Motion Picture Theaters industry in 573 Micropolitan Statistical Areas. The results are suggestive of fierce competition between theaters in the market for film exhibition rights.
Keywords: L13; C25; C73; 330; demand uncertainty; dynamic oligopoly; fiem entry and exit; Markov-perfect equilibrium; nested fixed point estimator; sunk costs; toughness of competition